DIRECT USAGE OF MINISCREW ANCHORAGE TO INTRUDE OVERERUPTED MAXILLARY POSTERIOR TEETH BEFORE PROSTHODONTIC PREPARATION:A CASE REPORT - Yasemin Bahar Acar; Mustafa Ateş (Istanbul University, 2016)
Overeruption of maxillary molars due loss of opposing teeth creates occlusal and functional interferences. Before reconstruction can be initiated, intrusion of overerupted molars becomes essential. This report illustrates treatment of overerupted maxillary premolar and molar via direct use of miniscrew anchorage. A 24-year old female had lost first and second left mandibular molars due to pulpal necrotizing agents, resulting with a large alveolar bone defect and overerupted maxillary premolar and molar. She had a history of unsuccessful alveolar distraction of mandibular left premolars to increase the alveolar bone height prior to implant placement. Patient was satisfied with her smile and refused comprehensive orthodontic treatment. Maxillary premolar and molar were intruded segmentally for 4mm in 8 months, using a combination of a mini-implant and partialfixed edgewise appliances. Biological responses of teeth and surrounding bony structures to intrusion appeared normal and acceptable in radiographic and clinical examination.